PENILAIAN AUTENTIK KOMPONEN MATEMATIKA PADA PEMBELAJARAN TEMATIK BERDASARKAN KURIKULUM 2013 DI KELAS IV SDN SEMANGAT DALAM 2 TAHUN PELAJARAN 2013/2014 - Rivilla, Sessi Rewetty; Jannah, Raudatul (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2015)
This study aims to determine how the authenticity evaluation mathematics component on thematic learning based on 2013 curriculum in class IV SDN 2 Semangat Dalam in academic year 2013/2014. This research is a field research using qualitative approach and descriptive method. Subject in this study is fourth grade teacher class C. While becoming object in this research is authentic evaluation Mathematics Components on Thematic Learning. The results showed that the mathematical component of authentic assessment on thematic learning based curriculum in 2013 in class IV SDN 2 Semangat Dalam in academic year 2013/2014 have not been fully able to carry out in accordance with the demands of the curriculum in 2013, but the activities undertaken by teachers has been implemented as expected in government 2013. In lesson plan, teacher has already contained authentic assessment such as observation, written test (exercise), assignments and performance assessment. Observation technique is used in implementation of the assessment to the teacher?s attitude, written test (exercises and assignments or homework are used to the teacher's knowledge competence assesment, whereas for competency skills of teachers use performance assessment. For the implementation of the examination in the end of the semester, teacher manages grades and reports student learning outcomes in SDN Semangat Dalam 2 based on school policy